Fundamentals of wavelets : theory, algorithms, and applications - Goswami, Jaideva C.; Chan, Andrew K. (Hoboken, N.J. : Wiley, 2010)
'Most existing books on wavelets are either too mathematical or they focus on too narrow a specialty. This book provides a thorough treatment of the subject from an engineering point of view. It is a one-stop source of theory, algorithms, applications, and computer codes related to wavelets. This second edition has been updated by the addition of: a section on'Other Wavelets' that describes curvelets, ridgelets, lifting wavelets, etc. a section on lifting algorithms Sections on Edge Detection and Geophysical Applications Section on Multiresolution Time Domain Method (MRTD) and on Inverse problems.'--
'Most existing books on wavelets are either too mathematical or they focus on too narrow a specialty. This book provides a thorough treatment of the subject from an engineering point of view. It is a one-stop source of theory, algorithms, applications, and computer codes related to wavelets. This second edition has been updated by the addition of: a section on'Other Wavelets' that describes curvelets, ridgelets, lifting wavelets, etc a section on lifting algorithms'--
Keywords: Wavelets (Mathematics); Image processing -- Mathematics; Electromagnetic waves -- Scattering -- Mathematical models; Boundary value problems